Facilitating and impeding factors affecting the activation of work improvement teams in government agencies. [article]. - Agra, Angela C.
The aim of the study was to determine the facilitating and impeding factors affecting the activation of work Improvement Teams in government agencies. Those which turned out to be positively related to activation were a)involvement and visibility of management in WIT-related activities, b)presence of feedback mechanisms for management rank and file regarding WIT matters, c)conduct of support activities d)recognition schemes and e)routine task performed by teams. The impeding factor to team activation was the difficulty of teams in identifying problems/ideas within their operational control.